Marketing research and pharmacoeconomic aspects of medicinal cosmetic products containing azelaic acid - O. Р. Kilieieva (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Goal. Analysis of the domestic market of pharmaceutical cosmetics containing azelaic acid, registered on the pharmaceutical market of Ukraine; determination of stability indicators of the range of drugs of this group, their competitiveness of solvency for further study of the availability of this list of drugs and the possibility of meeting the needs of the population in the treatment of the specified pathology.Materials and methods. The materials of the study became the legal basis: the orders of the Ministry of Health of Ukraine, the Protocol on the provision of medical care to patients with vulgar acne (Approved by the Order of the Ministry of Health of Ukraine of May 08, 2009, No. 312, with amendments № 670 dated 04.08.2016). Unified clinical protocol of primary, secondary (specialized), tertiary (highly specialized) medical care (acne).Methods of research - statistical, graphic, marketing, pharmacoeconomic, content analysis of official sources of information.Results. According to the unified clinical protocols of primary, secondary (specialized), tertiary (highly specialized) medical care (ACMD) about acne – this skin disease has the ICD-10 code: L70 in accordance with the International Statistical Classification of Diseases and Related Disorders of Health (Tenth Edition) - vulgar acne.In the occurrence of acne, four principal mechanisms are distinguished: increased production of sebum by sebaceous glands; increased keratinization of epidermis cells and the accumulation of horny cells in the ducts of the sebaceous glands (follicular hyperkeratinization); propionic acid bacteria (Propionibacterium acnes – microorganism, which normally lives in sebum without oxygen availability); inflammation.In analyzed literary sources, it is generally indicated that acne treatment should be of a complex nature. Except drug therapy should include such components as conversation with the patient and his psychological support, physiotherapy, daily skin care, local and systemic medical treatment.Conclusions. The assurance of the assortment's stability is carried out. It has been established that the assortment of azelaic acid-containing LCAs for the prevention and treatment of acne is stable (in pharmacies of Zaporizhzhia? Dnipro, Mykolaiv, Kryvyi Rih, Cherkasy) and is equal to 0.87. The coefficient of competitiveness is calculated. It has been established that the most competitive is AcneStop (Ukraine). The rate of liquidity of the price is calculated. Calculated values of Kliq indicate that the maximum ratio of liquidity to the drug is Azogel PRAT (gel) (Kliq = 0.49), and the minimum – on the LS Skinoren (cream) (Kliq = 0.05) and is more available on the market among analogues. Solvency adequacy ratio is calculated. According to the calculations it is clear that the highest index of Ca.s is Skinoren (gel, cream) – 5.7 %, lowest – Azogel PRAT (Ca.s = 1.2 %).